Nepotism in opposition 'worrying': Not healthy: Academics fear progress of other capable leaders will be blocked - Kapoor, Carisma (New Straits Times, 2012)
THE possibility of a cabinet consisting of several members of "elite families" could become a reality if the opposition coalition comes to power after the next general election.